Compiler development in Component-oriented Software Development (COSD): Issues and challenges - Aris H. (2023)
Software development based on the composition of the existing components, known as component-oriented software development (COSD) is a fast growing research area in the software engineering discipline. Amongst the various areas covered is the component-oriented specification language (COSL) development, which focuses on coming out with a dedicated specification language for COSD. This is required due to fact that the existing specification languages are insufficient if not unsuitable for COSD use. A number of works have been done in coming out with COSLs. However, these COSLs are not being accompanied by the construction of their compilers to complete the picture. The construction of compiler for COSL is currently not being given the attention it deserves. Therefore, in this paper, the need to construct the compiler for COSL is justified with the main focus given to the issues on the development of the COSL compiler and their corresponding challenges. Brief explanation on the phases of a compilation process is also included. 2005 IEEE.